(untitled) (International Journal of Environmental Sciences, 2024)
This work presents a frequency-reconfigurable microstrip patch antenna capable of operating at multiple resonant modes. In the OFF state, the antenna resonates at 8.17, 11.13, 15.77, and 17.46 GHz, while in the ON state it achieves resonances at 8.38, 11.13, 14.51, 16.20, 17.46, and 18.52 GHz. The reconfigurability is enabled through a single PIN diode, modeled and analyzed using HFSS, ensuring reliable switching between bands. The design covers both X-band (8–12 GHz) and Ku-band (12–18 GHz), making it suitable for modern multiband wireless communication. To enhance performance, square fractal slots are etched into the ground plane, resulting in improved bandwidth and gain characteristics. The antenna is realized on a low-cost FR-4 substrate (εr = 4.4, thickness = 1.6 mm). Simulation results confirm significant improvements in return loss, stable radiation patterns, and higher gain, demonstrating the antenna’s potential for advanced reconfigurable wireless systems.